Cytotoxic Activity of Unique Synthesized Five-membered Heterocyclic Compounds Coordinated with Tiopronin Monovalent - Sano, Naoyuki; Yoshino, Hironori; Sato, Yoshiaki; Honma, Hideo; Cordonier, Christopher E.J.; Kashiwakura, Ikuo (Current Pharmaceutical Design, 2023)
Background: We recently synthesized a compound in which 5-mercapto-1-methyltetrazole (MM4) was coordinated to tiopronin monovalent (TPN-Au(I)) and reported its cytotoxic activity against human leukemia cells in vitro. Objective: We further synthesized other heterocyclic compounds coordinated with TPN-Au(I) and assessed their cytotoxic activity against hepatocellular carcinoma HepG2 and lung cancer cell line H1299 in vitro. Methods: Seven kinds of compounds were synthesized by introducing a five-membered heterocyclic compound into TPN-Au(I). The number of viable cells was counted by a trypan blue dye exclusion assay. Fluorescence conjugated-Annexin V and propidium iodide were used for the apoptosis analysis. Results: Seven compounds were successfully synthesized. Among these compounds, TPN-Au(I)-MTZ (3- mercapto-1,2,4-triazole), TPN-Au(I)-MMT (2-mercapto-5-methyl-1,3,4-thiadiazole), and TPN-Au(I)-MMTT (2-mercapto-5-methylthio-1,3,4-thiadiazole) effectively suppressed the proliferation and induced apoptosis in HepG2 cells. In addition, TPN-Au(I)-MMTT and TPN-Au(I)-MMT also showed effective cytotoxicity against H1299 cells. Conclusion: The present results showed that introduction of some five-membered heterocyclic compounds, especially MMT and MMTT, to TPN-Au(I) improved the cytotoxicity against solid cancer cells.
Keywords: 3-mercapto-1